Optimization of The Use of The I-24/7 Network System by Bagkominter to Overcome Transnational Crime The Realization of Modern Police in The Era 4.0 - Nufani Puspita Sari; Basir - S; Lin - Yola (Faculty of Law, Universitas Pekalongan, 2023)
Indonesia has committed and is ready to implement Industry 4.0 to build a globally competitive manufacturing industry. Polri participates in supporting Indonesia towards the 4.0 era. Through precision towards modern policing, it is hoped that all police officers must be able to make good use of digital technology and continuously improve their capabilities in its implementation. The International Communications Section or abbreviated as Bagkominter has the main task of organizing and developing an information exchange system in efforts to prevent and eradicate international/transnational crimes through the INTERPOL network (I-24/7), ASEANAPOL and other information facilities; as well as collecting information and data processing. Based on the explanation described above, the problem will arise